The effect of rubber training on Kisame Tsuki's punch speed in Karate - Febryanti Nursaqinah; Tomoliyus Tomoliyus; Endang Rini Sukamti (International Journal Labs, 2024)
This research aims to determine: (1) the effect of rubber training on Kisame Tsuki's punches; (2) increase in Kisame Tsuki's punch speed. The design of this research is quantitative using a Two Group Pretest Posttest design, namely an experimental design carried out on two different groups, namely the rubber group and the control group. The population of this study were senior athletes aged 21 years and over. The sample for this study was 14 kumite athletes taken using a random sampling technique. The data analysis technique used was the Independent Sample T-test with a significance level of ? = 0.05. The research results are as follows. (1) There is an influence of rubber training on Kisame Tsuki Sig's punches. (2-tailed) (0.004) < 0.05 and also the calculated t value (3.613) > t table (2.447); (2) There was a significant increase in Kisame Tsuki's punch speed as seen from the rubber group's gain score of 0.49, which means there was a moderate increase. So training using rubber tools has an influence in increasing the speed of Kisame Tsuki's punches in UNJ Student Karate athletes.